2015
DOI: 10.1016/j.celrep.2015.08.056
|View full text |Cite
|
Sign up to set email alerts
|

The Deubiquitylating Enzyme USP4 Cooperates with CtIP in DNA Double-Strand Break End Resection

Abstract: DNA end resection is a highly regulated and critical step in DNA double-stranded break (DSB) repair. In higher eukaryotes, DSB resection is initiated by the collaborative action of CtIP and the MRE11-RAD50-NBS1 (MRN) complex. Here, we find that the deubiquitylating enzyme USP4 directly participates in DSB resection and homologous recombination (HR). USP4 confers resistance to DNA damage-inducing agents. Mechanistically, USP4 interacts with CtIP and MRN via a specific, conserved region and the catalytic domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 75 publications
1
65
0
Order By: Relevance
“…However, the intrinsic pro‐survival signalling could abolish the killing efficiency and lead to cisplatin tolerance and tumour development of melanoma 23, 24. Since that USP4 played a critical role in DNA damage response,16, 17 we proposed that the intervention of USP4 may affect cisplatin‐induced cell apoptosis in melanoma. To this end, we performed flow cytometry analysis to determine the cell apoptotic rate of cisplatin‐treated melanoma cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the intrinsic pro‐survival signalling could abolish the killing efficiency and lead to cisplatin tolerance and tumour development of melanoma 23, 24. Since that USP4 played a critical role in DNA damage response,16, 17 we proposed that the intervention of USP4 may affect cisplatin‐induced cell apoptosis in melanoma. To this end, we performed flow cytometry analysis to determine the cell apoptotic rate of cisplatin‐treated melanoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, USP4 is a rather important USP member with previously reported links to cancer associated‐DNA repair and p53 stability 15, 16, 17, 18. On the one hand, the elevated USP4 expression contributed to the growth of colorectal cancer via deubiquitination and stabilization of oncogene PRL‐3 19.…”
Section: Introductionmentioning
confidence: 99%
“…1A). Among them, USP1, USP4, USP11, and UCHL5 have been associated with HR (Wiltshire et al 2010;Murai et al 2011;Nishi et al 2014;Liu et al 2015;Orthwein et al 2015;Wijnhoven et al 2015). However, one of the hits, UCHL3, has not been implicated in DNA repair.…”
Section: Uchl3 Regulates Rad51 Ir-induced Focus Formation (Irif) and Hrmentioning
confidence: 99%
“…Yet it may be possible that RNF138 targets additional proteins involved in DSB repair pathway choice (Bekker-Jensen and Mailand, 2015). Interestingly, two independent studies have reported that the deubiquitinase (DUB) activity of USP4 functions in DNA-end resection (Liu et al, 2015; Wijnhoven et al, 2015). They both demonstrated that USP4 interacts with CtIP and MRN and regulates the recruitment of CtIP to DSBs.…”
Section: Ubiquitylation and Sumoylation Of The Dna-end Resection Machmentioning
confidence: 99%